Bipolar Radiofrequency Ablation Does Not Result in Full-Thickness Articular Cartilage Penetration: An Ex Vivo Bovine Investigation - Anthony N. Khoury, Ph.D; Maxwell J. Krupp, B.Sc; Andrea M. Matuska, Ph.D; Darren J. Friedman, M.D (Elsevier, 2022)
Purpose: To evaluate the depth of penetration of manufacturer-recommended bipolar radiofrequency (BRF) output in healthy hyaline cartilage. Methods: Two matched knees from a bovine specimen were harvested for immediate testing. BRF probes were used to treat the articular cartilage in a hydrated noncontact technique employing a 1-mm spacer on patellar, condylar, and trochlear surfaces. Two manufacturer-recommended ablate power settings were evaluated to analyze the effect of varying power outputs on the depth of penetration. Surfaces were randomized and treated with BRF ablate setting 3 (AB-3), 4 (AB-4), or left untreated as a control (12 grids each). Slices were extracted from treatment zones and subjected to fluorescein diacetate and propidium iodide viability stains and analyzed with confocal light microscopy. A general linear model was used to determine whether variables such as ablation setting, cartilage location, and side significantly influenced depth of penetration (DoP) and cartilage thickness (Minitab 19, Chicago, IL). When significance was noted (P < .05), a post hoc-Tukey test was used to investigate specific differences. Results: AB-3 had a 50.9% lower mean DoP than AB-4 (P = .006). The mean DoP was 237.9 ± 140.6 μm for AB-3 and 484.1 ± 267.0 μm for AB-4. Median DoP values were 243.2 ± 149.5 μm for AB-3, 51.2% lower than the 498.4 ± 286.0 μm for AB-4. The mean maximum DoP for AB-3 was 302.4 ± 167.8 μm, 50.6% lower than AB-4 value of 611.6 ± 299.1 μm. Analysis of the cartilage thickness confirmed there was no difference in overall cartilage thickness used for AB-3 versus AB-4 testing (P = .953). Conclusions: The RF probe ablate power setting AB-3 demonstrated significantly less articular cartilage depth of penetration than the AB-4 setting in a healthy bovine model. Clinical Relevance: Debridement of chondral lesions with plasma BRF is of clinical interest. The presented study adds basic science information for those considering performing this technique.